Hand hygiene opportunities on Canadian acute-care inpatient units: A multicenter observational study. (25th September 2018) - Nayyar, Dhruv; Moore, Christine; McCreight, Liz; Garvida, Chiana; Xu, Emily; Kiss, Alex; Ricciuto, Daniel R.; McGeer, Allison; Leis, Jerome A.
Abstract: In this multicenter observational study, medical and surgical inpatient rooms were randomized to receive 1 hour of continuous direct observation to determine hand hygiene opportunities (HHOs). After multivariable adjustment, HHOs were similar across inpatient units and hospitals. This estimate could serve to calibrate electronic hand hygiene monitoring systems for Canadian medical and surgical units.